Brain-Computer Interface Systems - Recent Progress and Future Prospects 2013
DOI: 10.5772/56135
|View full text |Cite
|
Sign up to set email alerts
|

A Review of P300, SSVEP, and Hybrid P300/SSVEP Brain- Computer Interface Systems

Abstract: Addi"ional informa"ion is available a" "he end of "he chap"er h""p://dx.doi.org/10.5772/56135 . IntroductionThere are several techniques for measuring brain activities such as magnetoencephalogram MEG , near infrared spectroscopy NIRS , electrocorticogram ECoG , functional magnetic resonance imaging fMRI , and electroencephalography EEG . Each technique has some advantages and disadvantages compared to other techniques. For example, in EEG the temporal resolution is high but the special resolution is low compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 42 publications
(86 reference statements)
0
48
0
6
Order By: Relevance
“…By using DFT, signal samples a 0 , a 1 , a 2 , a 3 , …, a N-1 , assuming a i ∊ R are transformed into series of harmonics A 0 , A 1 , A 2 , A 3 , …, A N-1 , assuming that A i ∊ C, it is done according to equation (2), where i -imaginary unit, k -harmonic number, n -signal sample number, a n -signal sample value, N -number of samples.…”
Section: Brain-computer Technology Inmentioning
confidence: 99%
See 1 more Smart Citation
“…By using DFT, signal samples a 0 , a 1 , a 2 , a 3 , …, a N-1 , assuming a i ∊ R are transformed into series of harmonics A 0 , A 1 , A 2 , A 3 , …, A N-1 , assuming that A i ∊ C, it is done according to equation (2), where i -imaginary unit, k -harmonic number, n -signal sample number, a n -signal sample value, N -number of samples.…”
Section: Brain-computer Technology Inmentioning
confidence: 99%
“…In practice, BCI technology is based on three paradigms: SCP, i.e. slow cortical potentials [2], induced potential P300 and ERD/ERS -event related desynchronization/synchronization [1].…”
Section: Introductionmentioning
confidence: 99%
“…Brain-Computer Interfaces (BCI) are an emerging input modality for disabled users seeking to communicate by computer [1,2]. BCI systems use brain signals directly as input to infer user intent.…”
Section: Introductionmentioning
confidence: 99%
“…In a comparative study, it was found that the overall spelling accuracies averaged for the same set of subjects, trials, and characters for RC, SC, and two variations of RB paradigms were 85, 72.2, 86.1, and 90.6%, respectively [14,69]. It is interesting to note that other than P300 BCI, application of RB paradigm has been extended to other BCI modalities too [54,[70][71][72].…”
Section: Region-based (Rb) Paradigmmentioning
confidence: 99%